[P257] Feasibility planning study to improve local control for muscle-invasive bladder cancer using theragnostic imaging and isotoxic dose escalation. (August 2018) - Rogers, Jane; Sherwood, Victoria; Wayte, Sarah; Duffy, Jon; Manolopoulos, Spyros
Abstract : Purpose: Outcomes for muscle-invasive bladder cancer (MIBC) have changed little over recent decades, with long-term survival remaining around 50% in the UK[1] . Standard radiotherapy treatment involves trans-urethral resection and uniform radiotherapy to the whole bladder. Visualisation of bladder tumour on computed tomography (CT) is poor, but diffusion-weighted magnetic resonance imaging (DW-MRI) provides good visibility of volumes of high tumour burden. Theragnostic imaging using DW-MRI could therefore enable dose escalation to such volumes, however, geometric distortion inherent in DW-MRI requires consideration. In this study geometric distortion was quantified and accounted for, and dose was escalated isotoxically to simulated tumours within the bladder, with calculation of corresponding increases in local control. The aim was to facilitate individualised patient treatments with biologically-adapted radiotherapy (BART) to isotoxically increase tumour control probability (TCP). Methods: An in-house bladder phantom was imaged using CT and DW-MRI and distortion in DW-MRI quantified. Tumours were simulated on a patient planning CT in various locations within the bladder and a margin added to accommodate distortion effects, emulating DW-MRI-registered images. Dose distributions were calculated with tumours receiving the maximum possible dose escalation beyond the standard 64 Gy in 32 fractions whilst maintaining normal tissue constraints, and bladder wall receiving 48 Gy, 52 Gy or 56 Gy. Poisson-based TCP models fitted to clinical trials data were used with clonogenic cell density assumed to be 10 7 cm - 3 in tumours and ranging between 0 and 10 7 cm - 3 within the bladder wall. Feasibility of delivery and effect on TCP was assessed via dose accumulation using cone beam CT. Results: Maximum dose escalation to 78 Gy was possible for all inferior tumours. Superior, anterior, posterior and lateral tumours could be isotoxically escalated to 70 Gy, 71 Gy, 72 Gy and 72 Gy respectively regardless of tumour volume. Corresponding improvements in TCP ranged from 6 – 8% for superior tumours to 10 – 15% for inferior tumours. Conclusions: Theragnostic imaging using DW-MRI was investigated for BART aiming to isotoxically increase TCP. This study indicates that such an approach could enable personalised radiotherapy treatment for MIBC and isotoxically improve outcomes.